Growing intradiploic epidermoid cyst presenting as a diagnostic challenge in the setting of Langerhans cell histiocytosis: A case report - Benjamin S. Fletcher, MD; Benjamin A. Johnson-Tesch, MD; John C. Benson, MD; Alex A. Nagelschneider, MD; Lisa M. Marinelli, MD; Dong Kun Kim, MD (Radiology Case Reports, 2025)
Epidermoid cysts (EC) are benign cystic lesions lined by squamous epithelium resulting from entrapped ectodermal elements during development. These can occur in various anatomic locations, including intracranial, intradiploic, spinal and in the superficial soft tissues. Although benign, these can grow or rupture, and mimic malignant tumor or infection. Here, we describe the case of an 8-month-old male with cutaneous Langerhans cell histiocytosis (LCH) presenting with a lytic calvarial lesion initially thought to be osseous involvement of LCH. Further workup revealed imaging findings discordant with this diagnosis and instead suggestive of an intradiploic EC which was subsequently confirmed with pathology. This case illustrates the importance of keeping the differential diagnosis broad and re-evaluating the diagnosis based on the imaging appearance despite the presumptive diagnosis provided clinically.